Investigation of the temperature-dependent behaviours of Li metal anode. Issue 66 (30th July 2019) - Guo, Yanpeng; Li, Dian; Xiong, Rundi; Li, Huiqiao
Abstract : Effects of temperature on Li nucleation/deposition behaviors and electro-chemical performances are thoroughly investigated in both ether and ester electrolytes. Abstract : Effects of temperature on Li nucleation/deposition behaviours and electrochemical performances are thoroughly investigated. Higher temperature leads to lower nucleation density with larger deposit sizes due to the reduced surface migration barrier and accelerated ion diffusion, plus better lifespans and coulombic efficiency owing to the relatively conducive morphology characteristics and a favorable SEI layer.